Ragam dan Unsur Spiritualitas pada Ilustrasi Naskah Nusantara 1800-1900-an - Nuning Damayanti; Haryadi Suadi (ITB Journal Publisher, LPPM ITB, 2007)
A civilized society is a society who respects the culture of its predecessors and their philosophy of life, including the inherited artifacts that represent cultural values. Accordingly, the cultural development of a society can be traced and valued from its traditional artifact, such as an ancient drawing/old illustration that passed from the older generation. Aside of its economical values, ancient drawing/old illustration is a cultural product that serves as an object of visual language or visual communication. Before script and writing were established, drawings were used by people from thousands years ago to establish communication. The discovery of pictures in the prehistoric caves is considered as the beginning of drawing tradition towards modern illustration. Yet, the discovery of scripts and writing devalue the tradition of drawing, although it is believed that pictures worth to be the simplest and the most effective communication among human. This research tried to identify how an ancient illustration/drawing is used as a mean to communicate, as well as understanding the society who created it. A hermeneutic reasoning was employed to explain the visuals of ancient illustration/ pictures. Illustrations/pictures from the old Java and Bali traditional visual arts until the first year of the 20th century were used as object of analyses. It was assumed that the selected objects carry visual communication means and spiritualism content that could be elaborated more, and thus provide rich understandings to learn from.